2021
DOI: 10.15503/jecs2021.2.505.526
|View full text |Cite
|
Sign up to set email alerts
|

European Cultural Heritage and Skills Development Course for Adult Learners’ Self-Development

Abstract: Aim. This article aims to evaluate the target course created and the development of adult learners’ 21st century skills during the course implementation in six EU countries. Concept. European Cultural Heritage and Skills Development Course is a culture-based blended-learning course created within the framework of the Erasmus+ project “Cultural Knowledge and Language Competences as a Means to Develop 21stCentury Skills” conducted in six EU countries: Croatia, Latvia, Slovenia, Romania, Poland and Czech Republic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It has to be added that a course trial was conducted, as suggested in the course framework, among 227 learners from these six countries in 2019, where the face-to-face stage was implemented in class. The results obtained indicate a higher skills’ development and greater student satisfaction (Luka, 2021a, 2021b), thus emphasizing the necessity of live interaction.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…It has to be added that a course trial was conducted, as suggested in the course framework, among 227 learners from these six countries in 2019, where the face-to-face stage was implemented in class. The results obtained indicate a higher skills’ development and greater student satisfaction (Luka, 2021a, 2021b), thus emphasizing the necessity of live interaction.…”
Section: Discussionmentioning
confidence: 81%
“…As the general concept of BL has been presented in depth in a previous article by the author (cf. Luka, 2021b), this literature review focuses on certain articles published during the COVID-19 pandemic on applying BL for AE that are relevant to the current research.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research aimed to obtain data on the differences between two groups of people who are territorially situated in the former state of Czechoslovakia. The study sought to point out the differences in the subjective perceptions of people in Central Europe who are mentally significantly close [24][25][26]. The study results related to the research were realised after the second wave of the pandemic situation of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The course concept, its creation and methodologies as well as the specificity of adult learners have been analysed in prior research by the author (cf. Luka, 2019a;Luka, 2019b;Luka, 2021;Luka, 2022).…”
Section: Course Descriptionmentioning
confidence: 99%